Positive electrode active material and lithium secondary battery including same
By forming lithium manganese-based oxides into core-shell particles and forming a barrier layer on their surface, the problem of transition metal dissolution in lithium secondary batteries is solved, and the rate performance and life of the battery are improved.
Patent Information
- Application Number
- CN202380061651.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-14
- Filing Date
- 2023-05-03
- Publication Date
- 2025-04-11
AI Technical Summary
The existing lithium-rich lithium manganese-based oxides have problems with low rate performance and reduced service life in lithium secondary batteries. This is mainly due to the dissolution of transition metals from the surface of oxide particles, resulting in impurities in the electrolyte and increasing the negative electrode resistance.
Dissolution of transition metal is suppressed or mitigated by forming the lithium manganese-based oxide into core-shell particles and forming a barrier layer on its surface. The specific method includes performing heat treatment at high temperature, using borate or other halogen as barrier layer components to form a protective layer on the surface of the lithium manganese-based oxide.
It effectively inhibits the dissolution of transition metals, reduces the formation of impurities, improves the rate performance and life of lithium secondary batteries, and maintains high stability especially under high voltage driving.
Smart Images

Figure BDA0005283254870000371 
Figure BDA0005283254870000381 
Figure BDA0005283254870000391
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the positive electrode active material. More specifically, the present invention relates to a positive electrode active material and a lithium secondary battery including the positive electrode active material. The positive electrode active material is a positive electrode active material including a lithium-rich lithium manganese-based oxide, which can prevent the reduction of the electrochemical characteristics of the lithium secondary battery including the rate characteristics due to the excessive presence of lithium and manganese in the lithium manganese-based oxide. In particular, the life of the lithium secondary battery can be prevented from being reduced by inhibiting or reducing the dissolution of transition metals from the lithium manganese-based oxide. Background Art
[0002] Batteries use materials that can undergo electrochemical reactions at the positive and negative electrodes to store electrical energy. A typical example of such batteries is a lithium secondary battery that stores electrical energy through the chemical potential difference when lithium ions are inserted / released between the positive and negative electrodes.
[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.
[0004] Representative materials used as positive electrode active materials for lithium secondary batteries include lithium composite oxides. Examples of the above-mentioned lithium composite oxides include LiCoO2, LiMn2O4, LiNiO2, LiMnO2, or complex composite oxides of nickel, cobalt, manganese or aluminum as disclosed in Korean Patent Publication No. 10-2015-0069334 (published on June 23, 2015).
[0005] Among the above-mentioned positive electrode active materials, LiCoO2 is the most widely used due to its excellent life characteristics and charge and discharge efficiency, but its price competitiveness is limited due to the resource limitation of cobalt used as a raw material and its high price.
[0006] Lithium manganese-based oxides such as LiMnO2 and LiMn2O4 have the advantages of excellent thermal stability and low price, but have problems of small capacity and poor high temperature characteristics. In addition, LiNiO2-based positive electrode active materials have battery performance with high discharge capacity, but are difficult to synthesize due to the cation mixing problem between lithium and transition metals, resulting in major problems in rate performance.
[0007] Furthermore, depending on the severity of such cation mixing, a large amount of lithium byproducts are generated, most of which are composed of compounds of LiOH and Li2CO3, so when preparing the positive electrode slurry, it leads to gelation, or after preparing the electrode, it may become a cause of gas generation due to repeated charge and discharge. In addition, the residual Li2CO3 in the above lithium byproducts increases the swelling phenomenon of the monomer and becomes a cause of reducing the service life.
[0008] Various candidate materials are being discussed for compensating for the shortcomings of these existing positive electrode active materials.
[0009] For example, research is underway to use lithium-rich manganese-based oxides containing excess manganese in transition metals and a lithium content greater than the total content of transition metals as positive electrode active materials for lithium secondary batteries. Such lithium-rich manganese-based oxides are also called overlithi ated layered oxides (OLO).
[0010] Although the above OLO has the advantage of showing high capacity under high voltage working environment in theory, in reality, due to the excessive manganese contained in the oxide, its conductivity is relatively low, so there is a disadvantage that the rate performance of the lithium secondary battery using OLO is low. As mentioned above, when the rate performance is low, the charge / discharge capacity and life efficiency (cycle capacity retention) deteriorate during the cycle of the lithium secondary battery.
[0011] Research has been conducted to change the composition of OLO in order to solve the above problems, but these attempts have not yet reached the level of commercialization. Summary of the invention
[0012] Technical issues
[0013] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles plays a leading role in the market, and the demand for positive electrode active materials used in lithium secondary batteries is also constantly changing.
[0014] For example, in the prior art, lithium secondary batteries using lithium iron phosphate (LFP) are mainly used from the viewpoint of ensuring safety, etc., but recently, the use of nickel-based lithium composite oxides having a larger energy capacity per unit weight than LFP has been expanded.
[0015] In addition, nickel-based lithium composite oxides, which are mainly used as positive electrode active materials for high-capacity lithium secondary batteries in recent years, must use ternary metal elements such as nickel, cobalt and manganese or nickel, cobalt and aluminum. However, since cobalt is not only unstable in supply and demand but also too expensive compared to other raw materials, a positive electrode active material with a new composition that can reduce the cobalt content or does not contain cobalt is needed.
[0016] Taking the whole situation into consideration, although lithium-rich lithium manganese-based oxides can meet the expectations of the above-mentioned market, the above-mentioned lithium manganese-based oxides still have the limitation of lacking electrochemical performance or stability in replacing commercial positive electrode active materials such as ternary lithium composite oxides composed of nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA).
[0017] For example, compared with ternary lithium composite oxides, lithium manganese-based oxides are more likely to have transition metals eluted from the particle surface during repeated charge and discharge. In particular, manganese contained in excess in lithium manganese-based oxides is more likely to be eluted from the particle surface.
[0018] When the transition metal is eluted from the lithium manganese-based oxide, the eluted transition metal may react with the electrolyte on the surface of the lithium manganese-based oxide to form impurities. The impurities not only increase the surface resistance of the lithium manganese-based oxide, but also become the cause of reducing the insertion / extraction efficiency of lithium ions through the lithium manganese-based oxide.
[0019] Furthermore, transition metals dissolved from the above-mentioned lithium manganese-based oxide or impurities formed by the reaction of the dissolved transition metals with the electrolyte may move to the negative electrode through the electrolyte as a medium and may be deposited on the surface of the negative electrode.
[0020] For example, due to a side reaction between the surface of the lithium manganese-based oxide and the electrolyte or a structural change (crystal structure change, etc.) of the lithium manganese-based oxide, the excessive amount of Mn contained in the lithium manganese-based oxide may be 2+ Mn dissolved in the electrolyte may be dissolved in the electrolyte. 2+ During the formation or charge-discharge process, the electrolyte may move to the negative electrode surface, thereby reacting with various substances (electrons, electrolyte, electrodes or by-products, etc.) present in the battery. As a result, Mn 2+ , Mn metal or Mn-containing compounds (e.g., MnCO3, MnO, MnF2, etc.) impurities exist.
[0021] Transition metals or impurities deposited on the surface of the negative electrode will rapidly increase the resistance of the negative electrode. This resistance anomaly is a representative cause of accelerated deterioration of the life of lithium secondary batteries.
[0022] In particular, in the case of a lithium secondary battery using the above-mentioned lithium manganese-based oxide as a positive electrode active material, the operating voltage is higher than that of a lithium secondary battery using other commercially available ternary lithium composite oxides as a positive electrode active material, so the above-mentioned problem is likely to occur.
[0023] However, there is currently no technology for addressing the dissolution of transition metals from lithium-rich lithium manganese-based oxides and the problems arising therefrom.
[0024] As described above, compared with other types of commercially available positive electrode active materials, existing lithium-rich lithium manganese-based oxides have disadvantages in electrochemical performance and / or stability. However, the inventors of the present invention have confirmed that when a barrier layer capable of controlling the overall composition of the lithium manganese-based oxide and inhibiting or reducing the dissolution of transition metals from the surface of the lithium manganese-based oxide is included, the lithium-rich lithium manganese-based oxide can also exhibit electrochemical performance and stability at a commercially available level.
[0025] In particular, the inventors of the present invention have confirmed that the dissolution of transition metals from the lithium manganese-based oxide can be suppressed or reduced by forming the lithium manganese-based oxide into core-shell particles in which at least one transition metal constituting the lithium manganese-based oxide has a concentration gradient from the core to the shell, and the content of the transition metal with a relatively low dissolution possibility in the region corresponding to the shell is made greater than the content of other transition metals.
[0026] Furthermore, the inventors of the present invention have confirmed that when the surface of the core-shell particle, i.e., the surface of the shell, is covered with a barrier layer capable of inhibiting the elution of transition metals from the core-shell particle, the elution of transition metals from the lithium manganese-based oxide can be further inhibited or reduced.
[0027] Therefore, the object of the present invention is to provide a positive electrode active material comprising a lithium-rich lithium manganese-based oxide, wherein the positive electrode active material can control the bulk phase composition of the lithium manganese-based oxide and simultaneously form a barrier layer on the surface of the lithium manganese-based oxide, thereby inhibiting or reducing the dissolution of transition metals in the lithium manganese-based oxide.
[0028] Furthermore, an object of the present invention is to provide a positive electrode active material, which simultaneously inhibits or reduces the dissolution of transition metals in the lithium manganese-based oxide and improves the charge transfer and / or diffusivity (i.e., surface kinetic properties) of lithium ions on the surface of the lithium manganese-based oxide by forming the lithium manganese-based oxide into core-shell particles in which at least one transition metal constituting the lithium manganese-based oxide has a concentration gradient from the core to the shell, and makes the content of the transition metal with a relatively low dissolution possibility in the region corresponding to the shell higher than that of other transition metals.
[0029] In addition, an object of the present invention is to provide a lithium secondary battery, which prevents the decrease in rate performance caused by the excessive presence of lithium and manganese in the existing OLO by using a positive electrode containing the positive electrode active material defined in this article, and in particular achieves high stability even when driven at high voltage by reducing the side reaction between the above-mentioned positive electrode active material and the electrolyte.
[0030] Solutions to the problem
[0031] According to one aspect of the present invention for solving the above-mentioned technical problems, there is provided a positive electrode active material, which includes a lithium manganese-based oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R-3m space group are solid-dissolved or complexed.
[0032] In the commonly commercialized ternary lithium composite oxides composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), the phase belonging to the R-3m space group exists as a single phase. However, the lithium-rich lithium manganese-based oxide defined in this article is characterized in that the phase belonging to the C2 / m space group and the phase belonging to the R-3m space group are solid-dissolved or complexed.
[0033] Here, the lithium manganese-based oxide is provided as core-shell particles in which at least one transition metal constituting the lithium manganese-based oxide has a concentration gradient from the core to the shell.
[0034] At this time, the lithium manganese-based oxide is formed into core-shell particles in which at least one transition metal constituting the lithium manganese-based oxide presents a concentration gradient from the core to the shell, and the content of the transition metal with a relatively low dissolution possibility in the region corresponding to the shell is made greater than the content of other transition metals, thereby reducing the possibility of transition metal dissolution from the lithium manganese-based oxide.
[0035] In one embodiment, the lithium manganese-based oxide in the positive electrode active material may be present in at least one form selected from a single primary particle and a secondary particle formed by aggregation of a plurality of primary particles.
[0036] For example, the positive electrode active material may include the lithium manganese-based oxide as secondary particles formed by aggregation of a plurality of primary particles.
[0037] Here, the secondary particle may be a core-shell particle, and the core-shell particle exhibits a concentration gradient of at least one transition metal from a center portion of the secondary particle toward a surface portion of the secondary particle.
[0038] In this case, the barrier layer may be present in a manner of covering at least a portion of the surface of the secondary particle, thereby suppressing or reducing the elution of the transition metal from the secondary particle.
[0039] Furthermore, a grain boundary is defined between adjacent primary particles in the secondary particles. The barrier layer may exist in a state of being diffused from the surface of the secondary particle toward the center of the secondary particle along the grain boundary.
[0040] In yet another embodiment, the primary particle may be a core-shell particle, and the core-shell particle presents a concentration gradient of at least one transition metal from the center of the primary particle toward the surface of the primary particle.
[0041] In this case, the barrier layer exists so as to cover at least a part of the surface of the primary particle, thereby being able to suppress or reduce the elution of the transition metal from the primary particle.
[0042] In another embodiment, the primary particle may include at least one crystal grain, and the crystal grain may present a concentration gradient of at least one transition metal from a center portion of the crystal grain toward a surface portion of the crystal grain.
[0043] In this case, the barrier layer may cover each crystal grain in the primary particle one by one, but the purpose of suppressing or reducing the elution of the transition metal can be fully achieved by covering the surface of the primary particle.
[0044] In one embodiment, the lithium manganese-based oxide may be represented by the following Chemical Formula 1.
[0045] [Chemical formula 1]
[0046] Li(Li a M1 x M2 y ) 2-b X b
[0047] (Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd and Nd, M2 and M1 are not repeated, X is a halogen that can replace at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, <a≤0.7、0≤b≤0.1、0<x≤1、0≤y<1、0<x+y≤1)。
[0048] In another embodiment, the lithium manganese-based oxide may be represented by the following Chemical Formula 1-1.
[0049] [Chemical formula 1-1]
[0050] rLi2MnO 3-b" X'b" ·(1-r)Li a' M1 x' M2 y' O 2-b' X b'
[0051] (Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd and Nd, M2 and M1 are not repeated, X and X' are halogens that can replace at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, <r≤0.7、0<a'≤1、0≤b'≤0.1、0≤b"≤0.1、0<x'≤1、0≤y'<1、0<x'+y'≤1)。
[0052] Furthermore, according to another aspect of the present invention, a positive electrode including the positive electrode active material is provided.
[0053] In addition, according to another aspect of the present invention, a lithium secondary battery using the positive electrode is provided.
[0054] Effects of the Invention
[0055] According to the present invention, the limitations of existing lithium-rich lithium manganese-based oxides which are still inferior in electrochemical performance and / or stability compared with commercial ternary lithium composite oxides composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) can be improved.
[0056] Specifically, according to the present invention, the lithium manganese-based oxide is formed into core-shell particles in which at least one transition metal constituting the lithium manganese-based oxide presents a concentration gradient from the core to the shell, and the content of the transition metal with a relatively low possibility of dissolution in the region corresponding to the shell is made greater than the content of other transition metals, thereby suppressing or reducing the dissolution of the transition metal from the lithium manganese-based oxide.
[0057] Furthermore, when the surface of the core-shell particle, i.e., the surface of the shell, is covered with a barrier layer capable of inhibiting or reducing the dissolution of transition metals from the core-shell particle, the dissolution of transition metals from the lithium manganese-based oxide can be further inhibited or reduced.
[0058] By suppressing or reducing the elution of the transition metal from the lithium manganese-based oxide, it is possible to prevent the transition metal eluted to the surface of the lithium manganese-based oxide from reacting with the electrolyte to form impurities.
[0059] The transition metal dissolved from the lithium manganese-based oxide and / or the impurities formed by the reaction of the dissolved transition metal with the electrolyte may move to the negative electrode with the electrolyte as the medium, and the impurities may be deposited on the surface of the negative electrode, resulting in a sharp increase in the resistance of the negative electrode. Therefore, as described in the present invention, it is necessary to limit the unintentional movement of the transition metal in the lithium secondary battery.
[0060] That is, according to the present invention, by preventing transition metals from eluting from the lithium manganese-based oxide, impurities are deposited on the positive electrode and / or the negative electrode due to the transition metals eluted from the lithium manganese-based oxide, thereby preventing the lithium secondary battery from accelerating its life deterioration.
[0061] Furthermore, according to the present invention, by forming the lithium manganese-based oxide into core-shell particles in which at least one transition metal constituting the lithium manganese-based oxide has a concentration gradient, the charge transfer and / or diffusivity (i.e., surface kinetic properties) of lithium ions on the surface of the lithium manganese-based oxide can be improved.
[0062] As described above, when a positive electrode including the positive electrode active material defined in this article is used, the rate performance degradation caused by the excessive presence of lithium and manganese in the existing OLO can be prevented, and in particular, high stability can be achieved even when driven at a high voltage by reducing the side reaction between the above-mentioned positive electrode active material and the electrolyte.
[0063] In addition to the above-described effects, specific effects of the present invention will be described while explaining specific details for implementing the present invention. DETAILED DESCRIPTION
[0064] Specific terms are defined herein for ease of understanding. Unless specifically defined herein, scientific terms and technical terms used herein should have the meanings commonly understood by those skilled in the art. In addition, it should be understood that as used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form, and vice versa.
[0065] Hereinafter, a positive electrode active material including a lithium-rich lithium manganese-based oxide and a lithium secondary battery including the positive electrode active material according to the present invention will be described in more detail.
[0066] Positive active material
[0067] According to one aspect of the present invention, there is provided a positive electrode active material, comprising a lithium manganese-based oxide in which a phase belonging to a C2 / m space group and a phase belonging to an R-3m space group are solid-dissolved or complexed.
[0068] The lithium manganese-based oxide contains at least lithium, nickel and manganese. In this case, in the lithium manganese-based oxide, the content of lithium in the lithium manganese-based oxide is greater than the sum of the contents of other transition metals (the molar ratio of lithium to all metal elements other than lithium in the lithium manganese-based oxide is generally greater than 1), so it is also called overlithiated layered oxide (OLO).
[0069] Generally speaking, considering that the manganese content in the total metal elements other than lithium in the commercial nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxide is less than 20 mol%, the above-mentioned lithium manganese-based oxide has a relatively high ratio of manganese in the total metal elements compared to the commercial ternary lithium composite oxide (for example, more than 50 mol%, preferably, 55 mol% to 75 mol%).
[0070] Furthermore, considering that the content of nickel in the total metal elements other than lithium in the commercial ternary lithium composite oxide composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) is more than 60 mol % (in the case of high-nickel lithium composite oxide, more than 80 mol %), the above-mentioned lithium manganese-based oxide has a relatively low ratio of nickel in the total metal elements (for example, less than 50 mol %, preferably, 25 mol % to 45 mol %) compared with the commercial ternary lithium composite oxide.
[0071] There is also a difference that the lithium / metal molar ratio measured from the lithium manganese-based oxide defined herein is greater than the lithium / metal molar ratio of a ternary lithium composite oxide such as nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA). For example, the lithium / metal molar ratio of a ternary lithium composite oxide such as nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA) appears to be close to 1. On the other hand, the lithium / metal molar ratio of the lithium manganese-based oxide defined herein is greater than 1, preferably 1.1 to 1.6.
[0072] Despite the above-mentioned difference in composition, the above-mentioned lithium manganese-based oxide can also be used as a composite metal oxide capable of intercalating / deintercalating lithium ions.
[0073] The lithium manganese-based oxide contained in the positive electrode active material defined herein may be present in the form of particles including at least one primary particle.
[0074] When the lithium manganese-based oxide exists as a single primary particle, the lithium manganese-based oxide may be referred to as a single particle. On the other hand, when the lithium manganese-based oxide exists as an aggregate formed by agglomerating a plurality of primary particles, the lithium manganese-based oxide may be referred to as a secondary particle.
[0075] The positive electrode active material may include at least one selected from the group consisting of a lithium manganese-based oxide present as a single particle and a lithium manganese-based oxide present as a secondary particle formed by agglomerating a plurality of primary particles.
[0076] The primary particles constituting the lithium manganese-based oxide may have a rod (bar) shape, an elliptical shape and / or an irregular shape. In addition, unless specifically designed during the manufacturing process, primary particles of various shapes exist in the same positive electrode active material.
[0077] The average particle size of the primary particles constituting the lithium manganese-based oxide defined herein may be 0.1 μm to 5 μm, preferably 0.1 μm to 1.0 μm, more preferably 0.25 μm to 0.75 μm. At this time, as the average particle size of the primary particles, the average value of the length in the major axis direction and the length in the minor axis direction of the primary particles ([major axis length + minor axis length] / 2) may be used.
[0078] When the lithium manganese-based oxide exists as secondary particles formed by aggregation of a plurality of primary particles, the secondary particles may have an average particle size of 0.5 μm to 15 μm. The average particle size of the secondary particles may vary depending on the number of the primary particles constituting the secondary particles.
[0079] Unless otherwise defined, the term "surface of the primary particle" as used herein refers to the outer surface of the primary particle exposed to the outside. Similarly, the term "surface of the secondary particle" as used herein refers to the outer surface of the secondary particle exposed to the outside. In this case, the "surface of the secondary particle" formed by the agglomeration of multiple primary particles is equivalent to the exposed surface of the primary particle existing on the surface of the secondary particle.
[0080] In addition, unless otherwise defined, the term "surface portion of a particle" as used herein refers to an area relatively close to the "surface" of a particle, and the "center portion of a particle" refers to an area relatively close to the "exact center" of a particle compared to the above-mentioned "surface portion". Therefore, the "surface portion of a primary particle" refers to an area relatively close to the "surface" of the above-mentioned primary particle, and the "center portion of a primary particle" refers to an area relatively close to the "exact center" of the above-mentioned primary particle compared to the above-mentioned "surface portion". Similarly, the "surface portion of a secondary particle" refers to an area relatively close to the "surface" of the above-mentioned secondary particle, and the "center portion of a secondary particle" refers to an area relatively close to the "exact center" of the above-mentioned secondary particle compared to the above-mentioned "surface portion".
[0081] At this time, a region other than the “surface portion of the particle” within any particle can be defined as the “center portion of the particle”.
[0082] For example, when the radius of the primary particle is r, the region at a distance of 0 to 0.5r from the surface of the primary particle can be defined as the surface portion of the primary particle, and the region at a distance of 0 to 0.5r from the exact center of the primary particle can be defined as the central portion of the primary particle. If the radius of the primary particle is 0.5 μm, the surface portion of the primary particle can be defined as the region at a distance of 0 to 0.25 μm from the surface of the primary particle, and the central portion of the primary particle can be defined as the region at a distance of 0 to 0.25 μm from the exact center of the primary particle.
[0083] In addition, as needed, when the radius of the above-mentioned primary particle is r, the area at a distance of 0 to 0.1r or 0 to 0.2r from the surface of the above-mentioned primary particle can be defined as the surface part of the above-mentioned primary particle, and the area at a distance of 0 to 0.2r or 0 to 0.5r from the exact center of the above-mentioned primary particle can be defined as the central part of the above-mentioned primary particle.
[0084] Similarly, when the radius of the secondary particle is r, the region at a distance of 0 to 0.5r from the surface of the secondary particle can be defined as the surface portion of the secondary particle, and the region at a distance of 0 to 0.5r from the exact center of the secondary particle can be defined as the central portion of the secondary particle. If the radius of the secondary particle is 2.0 μm, the surface portion of the secondary particle can be defined as the region at a distance of 0 to 1.0 μm from the surface of the secondary particle, and the central portion of the secondary particle can be defined as the region at a distance of 0 to 1.0 μm from the exact center of the secondary particle.
[0085] In addition, as needed, when the radius of the above-mentioned secondary particle is r, the region with a distance of 0 to 0.1r or 0 to 0.2r from the surface of the above-mentioned secondary particle can be defined as the surface portion of the above-mentioned secondary particle, and the region with a distance of 0 to 0.2r or 0 to 0.5r from the exact center of the above-mentioned secondary particle can be defined as the central portion of the above-mentioned secondary particle.
[0086] The lithium manganese-based oxide defined herein may be a lithium-rich lithium manganese-based oxide represented by the following Chemical Formula 1. The composition represented by the following Chemical Formula 1 may represent an average composition reflecting the composition of the barrier layer present in at least a portion of the surface of the lithium manganese-based oxide.
[0087] [Chemical formula 1]
[0088] Li(Li a M1 x M2 y ) 2-b X b
[0089] Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd and Nd, M2 and M1 are not repeated, X is a halogen capable of replacing at least some of the oxygen present in the above-mentioned lithium manganese-based oxide, and 0 <a≤0.7,0<b≤0.1,0<x≤1,0≤y<1,0<x+y≤1。
[0090] As the kind of halogen that can be used as X, referring to the periodic table, F, Cl, Br and / or I etc. can be used, and preferably F can be used.
[0091] A ratio of at least one selected from x and y in Chemical Formula 1 may be formed to have a gradient that changes from a surface portion of the primary particle toward a center portion of the primary particle.
[0092] Also, a ratio of at least one selected from x and y in Chemical Formula 1 may be formed to have a gradient that changes from a surface portion of the secondary particle toward a center portion of the secondary particle.
[0093] In addition, the lithium-rich lithium manganese-based oxide represented by the above Chemical Formula 1 may further include a spinel phase in addition to the phase belonging to the C2 / m space group and the phase belonging to the R-3m space group.
[0094] In another embodiment, the lithium manganese-based oxide may be represented by the following chemical formula 1-1. The composition represented by the following chemical formula 1-1 may represent an average composition reflecting the composition of the barrier layer present in at least a portion of the surface of the lithium manganese-based oxide.
[0095] [Chemical formula 1-1]
[0096] rLi2MnO 3-b" X' b" ·(1-r)Li a' M1 x' M2 y' O 2-b' X b'
[0097] Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd and Nd, M2 and M1 are not repeated, X and X' are halogens that can replace at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, <r≤0.7,0<a'≤1,0≤b'≤0.1,0≤b"≤0.1,0<x'≤1,0≤y'<1,0<x'+y'≤1。
[0098] As the kind of halogen that can be used as X and X', referring to the periodic table, F, Cl, Br and / or I etc. can be used, and preferably, F can be used.
[0099] In the above Chemical Formula 1 and the above Chemical Formula 1-1, when M1 is Ni, M2 may include Mn, and when M1 is Mn, M2 may include Ni. In addition, when M1 is Ni and Mn, M2 may not exist, or, if present, may be an element other than Ni and Mn.
[0100] That is, when M1 is Ni, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd and Nd (preferably, at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably, at least one selected from Co, P, B, Si, Ti, Zr and W, and further preferably, at least one selected from P, B and Si) and Mn.
[0101] When M1 is Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd and Nd (preferably, at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably, at least one selected from Co, P, B, Si, Ti, Zr and W, further preferably, at least one selected from P, B and Si) and Ni.
[0102] When M1 is Ni and Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd and Nd, preferably, may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably, may include at least one selected from Co, P, B, Si, Ti, Zr and W, further preferably, may include at least one selected from P, B and Si.
[0103] The lithium manganese-based oxide represented by the above chemical formula 1 or the above chemical formula 1-1 may optionally include cobalt. In addition, when the above lithium manganese-based oxide includes cobalt, the molar number of the above cobalt relative to the molar number of the entire metal element in the above lithium manganese-based oxide may be 20% or less, preferably, 15% or less, and more preferably, 10% or less. In another case, the lithium manganese-based oxide represented by the above chemical formula 1 may have a cobalt-free composition that does not contain cobalt.
[0104] The lithium / metal molar ratio measured from the lithium manganese-based oxide represented by the above chemical formula 1 or the above chemical formula 1-1 may be greater than 1, preferably, may be 1.1 to 1.6. Only when the lithium / metal molar ratio measured from the above lithium manganese-based oxide is at least greater than 1, can a lithium-rich lithium manganese-based oxide be formed. In addition, in order to allow the above lithium manganese-based oxide to properly form a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R-3m space group solid solution or complex, and at the same time exert a high capacity under a high voltage working environment, the lithium / metal molar ratio of the above lithium manganese-based oxide is preferably 1.1 to 1.6.
[0105] In addition, in order to properly form a solid solution or a complex solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R-3m space group, the manganese content in all metal elements other than lithium present in the lithium manganese-based oxide represented by the above Chemical Formula 1 or the above Chemical Formula 1-1 is preferably 50 mol% or more.
[0106] In order to make the above-mentioned lithium manganese-based oxide have the characteristics of high-capacity OLO under high-voltage working environment, the content of manganese in all metal elements except lithium present in the above-mentioned lithium manganese-based oxide is preferably 50 mol% or more and less than 80 mol%, more preferably 55 mol% to 75 mol%. When the content of manganese in the above-mentioned lithium manganese-based oxide exceeds 80 mol%, a phase change may occur during the formation and / or operation of the lithium secondary battery due to the movement of the transition metal (especially manganese) in the above-mentioned lithium manganese-based oxide. The above-mentioned phase change forms a spinel phase, and the above-mentioned spinel phase acting as an impurity in the above-mentioned lithium manganese-based oxide can cause a decrease in charge / discharge capacity or voltage decay when the lithium secondary battery is cycled.
[0107] In order to properly form a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R-3m space group in a solid solution or a complex, the content of nickel among all metal elements other than lithium present in the lithium manganese-based oxide represented by the above Chemical Formula 1 or the above Chemical Formula 1-1 is preferably less than 50 mol%.
[0108] When the nickel content in the above-mentioned lithium manganese-based oxide is above 50 mol%, it is difficult to fully form the C2 / m phase, or the phase belonging to the C2 / m space group and the phase belonging to the R-3m space group may not form a sufficient solid solution, resulting in phase separation during the formation and / or operation of the lithium secondary battery.
[0109] In addition, as will be described below, in order to ensure that nickel is sufficiently present on the surface of the lithium manganese-based oxide provided as core-shell particles forming a transition metal concentration gradient within the particles, the nickel content in the lithium manganese-based oxide is preferably 25 mol % to 45 mol %.
[0110] Generally, in a commercially available ternary lithium composite oxide composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), a phase belonging to the R-3m space group exists as a single phase.
[0111] On the other hand, the lithium-rich lithium manganese-based oxide represented by the above Chemical Formula 1 or the above Chemical Formula 1-1 is composed of rLi2MnO 3-b" X' b" The oxides of the phase belonging to the C2 / m space group (hereinafter referred to as "C2 / m phase") and (1-r)Li a' M1 x' M2 y' O 2-b' X b' The present invention provides a composite oxide formed by solid solution or complexation of an oxide belonging to a phase of the R-3m space group (hereinafter referred to as "R-3m phase"). For example, the lithium manganese-based oxide may exist in a state where an oxide of the C2 / m phase and an oxide of the R-3m phase form a solid solution.
[0112] In this case, a composite oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R-3m space group are simply physically and / or chemically bonded or combined does not correspond to the solid solution defined herein.
[0113] For example, a composite oxide having a phase belonging to the C2 / m space group whose surface is coated with a metal oxide belonging to the R-3m space group by mixing a metal oxide having a phase belonging to the C2 / m space group and a metal oxide having a phase belonging to the R-3m space group does not correspond to the solid solution defined in this article.
[0114] In the lithium manganese-based oxide represented by the above chemical formula 1-1, when r exceeds 0.7, Li2MnO as an oxide of the C2 / m phase in the above lithium manganese-based oxide 3-b" X' b" The ratio of R-3m to C2 / m phase oxide is excessively increased, which may lead to excessive increase in the manganese content in the positive electrode active material and decrease in discharge capacity. That is, in order to fully activate the C2 / m phase oxide with relatively high resistance in the above-mentioned lithium manganese-based oxide to improve the surface dynamics, the R-3m phase oxide is preferably present in a predetermined ratio or more.
[0115] The lithium manganese-based oxide as defined herein exists as core-shell particles in which at least one transition metal constituting the lithium manganese-based oxide has a concentration gradient from the core to the shell. At this time, by making the content of the transition metal with a relatively low dissolution possibility in the region corresponding to the shell higher than the content of other transition metals, the dissolution of the transition metal from the lithium manganese-based oxide can be suppressed or reduced.
[0116] Furthermore, by forming the lithium manganese-based oxide into core-shell particles in which at least one transition metal constituting the lithium manganese-based oxide has a concentration gradient, the charge transfer and / or diffusivity of lithium ions on the surface of the lithium manganese-based oxide (i.e., surface dynamic performance) can be improved.
[0117] When the concentration of transition metals present in the shell (or surface portion) and the core (or center portion) of any particle is different, the particle may be referred to as a core-shell particle. That is, the lithium manganese-based oxide is a core-shell particle, and the average composition of all metal elements constituting the lithium manganese-based oxide in the core and the shell may be different. Thus, the ratio of the phase belonging to the C2 / m space group and the phase belonging to the R-3m space group in the core and the ratio of the phase belonging to the C2 / m space group and the phase belonging to the R-3m space group in the shell may be different.
[0118] The shell may occupy at least a portion of the surface of the core. That is, the shell may be partially present on the surface of the core or may completely occupy the surface of the core.
[0119] In this article, when the molar number of all metal elements in the lithium manganese-based oxide is M 1 , the molar number of nickel is M 2 When M is calculated from the average composition of all metal elements in the core of the above lithium manganese-based oxide 2 / M 1 and M calculated from the average composition of all metal elements in the shell of the above lithium manganese-based oxide 2 / M 1 Can be different from each other.
[0120] As is well known, in the case of lithium-rich lithium manganese-based oxides containing excess manganese, the electrical conductivity is lower than that of lithium cobalt oxides or nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA) ternary lithium composite oxides containing relatively excess nickel. In addition, ternary lithium composite oxides also have the problem that the electrical conductivity decreases as the manganese content increases.
[0121] Various reactions occur on the surface of the various types of positive electrode active materials mentioned above. As the manganese content in the positive electrode active material increases, the movement and / or diffusion of lithium ion charges on the surface is hindered. This phenomenon can be called a decrease in surface kinetics or surface intra-reaction kinetics.
[0122] As described above, the lithium manganese-based oxide defined herein can improve the surface dynamic properties of the lithium manganese-based oxide by forming a transition metal concentration gradient between the core and the shell. This effect can be achieved by the transition metal concentration difference between the core and the shell of the primary particle, secondary particle, grain and / or single particle described below or the transition metal concentration gradient formed between the core and the shell.
[0123] In one embodiment, the lithium manganese-based oxide in the positive electrode active material exists in at least one form selected from a single primary particle and a secondary particle formed by agglomeration of multiple primary particles, so that the primary particle can be a core-shell particle in which at least one transition metal presents a concentration gradient from the center of the primary particle to the surface of the primary particle. The lithium manganese-based oxide existing as the secondary particle can be an aggregate of primary particles existing as core-shell particles.
[0124] When the primary particles are present as core-shell particles showing a concentration gradient of at least one transition metal from the core toward the shell, the surface dynamic properties of the primary particles and / or the secondary particles may be improved.
[0125] For example, at least one selected from nickel and manganese in the primary particles may present a concentration gradient from the core to the shell. More specifically, the primary particles may present a concentration gradient in which the concentration of nickel increases from the core to the shell, while the concentration of manganese decreases from the core to the shell.
[0126] In addition, when the transition metal presents a concentration gradient from the core to the shell of the primary particle, the rapid change of the metal element concentration between the core and the shell of the primary particle can be reduced. The crystal structure of the primary particle can be prevented from becoming unstable by preventing the rapid change of the metal element concentration in the primary particle.
[0127] In the primary particles in the form of core-shell particles, when the region where the concentration gradient of the transition metal exists is referred to as the shell of the primary particles, the average thickness of the shell may be 0.1 nm to 2 μm, preferably, 50 nm to 1 μm. When the thickness of the shell in the primary particles is less than 0.1 nm, it may be difficult to fully improve the surface dynamic properties of the primary particles. On the other hand, if the thickness of the shell in the primary particles is greater than 2 μm, it may be detrimental to the high capacity in a high voltage working environment, which is one of the advantages of the lithium manganese-based oxide.
[0128] In another embodiment, the primary particle may include at least one crystal grain. In this case, the crystal grain is in the core-shell form, and at least one transition metal may be in a concentration gradient from the center of the crystal grain to the surface of the crystal grain.
[0129] For example, the crystal grains may present a concentration gradient of at least one selected from nickel and manganese from the center to the surface. More specifically, the crystal grains may present a concentration gradient in which the concentration of nickel increases and the concentration of manganese decreases from the center to the surface.
[0130] When the primary particle includes a plurality of crystal grains, the plurality of crystal grains constituting the primary particle may have the core-shell structure. The crystal grains having the core-shell structure can not only stabilize the crystal structure of the primary particle, but also help improve the low conductivity of the lithium manganese-based oxide.
[0131] The region having the transition metal concentration gradient in the above-mentioned grains in the above-mentioned core-shell form exists in the region adjacent to the surface of the above-mentioned grains, and the average thickness of the region having the transition metal concentration gradient in the above-mentioned grains can be 0.1nm to 500nm. If the thickness of the region having the transition metal concentration gradient in the above-mentioned grains is less than 0.1nm, it may be difficult to fully improve the surface dynamic properties of the above-mentioned grains and the above-mentioned primary particles composed of the above-mentioned grains. On the other hand, if the thickness of the region having the transition metal concentration gradient in the above-mentioned grains is greater than 500nm, it may be detrimental to exerting the high capacity under high voltage working environment, which is one of the advantages of the above-mentioned lithium manganese-based oxide.
[0132] In another embodiment, the secondary particles may be core-shell particles in which at least one transition metal presents a concentration gradient from the center of the secondary particles to the surface of the secondary particles.
[0133] For example, at least one selected from nickel and manganese in the secondary particles may present a concentration gradient from the core to the shell. More specifically, the secondary particles may present a concentration gradient in which the concentration of nickel increases from the core to the shell, while the concentration of manganese decreases from the core to the shell.
[0134] In the secondary particles in the form of core-shell particles, when the region where the concentration gradient of the transition metal exists is referred to as the shell of the secondary particles, the average thickness of the shell may be 0.1 nm to 5 μm, preferably, 100 nm to 2 μm. When the thickness of the shell in the secondary particles is less than 0.1 nm, it may be difficult to fully improve the surface dynamic properties of the secondary particles. On the other hand, if the thickness of the shell in the secondary particles is greater than 5 μm, it may not be conducive to exerting the high capacity in a high voltage working environment, which is one of the advantages of the lithium manganese-based oxide.
[0135] The concentration gradient present in the primary particles, secondary particles and / or grains may suppress and / or mitigate phase changes that occur as transition metals in the particles migrate in unintended directions.
[0136] Furthermore, when the content of the transition metal with a relatively low possibility of dissolution in the region corresponding to the shell is made higher than the content of other transition metals, the dissolution of the transition metal from the lithium manganese-based oxide can be suppressed or reduced. By suppressing or reducing the dissolution of the transition metal from the lithium manganese-based oxide, the transition metal dissolved to the surface of the lithium manganese-based oxide can be prevented from reacting with the electrolyte to form impurities.
[0137] When the surface of the core-shell particle as defined herein, ie, the surface of the shell, is covered with a barrier layer capable of inhibiting the elution of transition metal from the core-shell particle, the elution of transition metal from the lithium manganese-based oxide can be further inhibited or reduced.
[0138] When the secondary particles exist as core-shell particles, the barrier layer can suppress or reduce the dissolution of transition metals from the secondary particles to the outside by covering at least a portion of the surface of the secondary particles. In addition, since the barrier layer covers the surface of the secondary particles, side reactions between the surface of the secondary particles and the electrolyte can be prevented.
[0139] When the barrier layer covers a portion of the surface of the secondary particle, the barrier layer may exist in an island shape. That is, even if the barrier layer covers at least a portion of the surface of the secondary particle in an island shape, the dissolution of the transition metal may be suppressed or mitigated by the area covered by the barrier layer. Therefore, the presence of the barrier layer on the surface of the secondary particle should be distinguished from the presence of the lithium manganese-based oxide and the heterogeneous oxide in a dispersed state on the surface of the secondary particle.
[0140] In addition, a grain boundary is defined between adjacent primary particles in the secondary particle, and the barrier layer may exist in a state of diffusing from the surface of the secondary particle toward the center of the secondary particle along the grain boundary. As the barrier layer diffuses toward the center of the secondary particle, the element mainly contained in the barrier layer may show a concentration gradient that decreases from the surface of the secondary particle toward the center of the secondary particle.
[0141] By forming the barrier layer with a gradient from the surface portion of the secondary particle toward the center portion of the secondary particle, it is possible to effectively suppress or reduce the elution of transition metal mainly from the surface portion of the secondary particle.
[0142] A part of the elements mainly included in the above-mentioned barrier layer may be doped into the above-mentioned primary particles and / or the above-mentioned secondary particles.
[0143] The barrier layer covering the surface of the secondary particle preferably has an average thickness of 0.1 nm to 1 μm.
[0144] When the average thickness of the barrier layer covering the secondary particles is less than 0.1 nm, it may be difficult to fully suppress the dissolution of transition metals from the secondary particles. On the other hand, when the average thickness of the barrier layer covering the secondary particles is thicker than 1 μm, the surface dynamic properties of the secondary particles may be reduced, or the electrical conductivity of the secondary particles may be reduced.
[0145] When the primary particles exist as core-shell particles, the barrier layer can suppress or reduce the dissolution of transition metals from the primary particles to the outside by covering at least a portion of the surface of the primary particles. In addition, since the barrier layer covers the surface of the primary particles, side reactions between the surface of the primary particles and the electrolyte can be prevented. At this time, the barrier layer can cover at least a portion of the surface of the secondary particles by covering the surface of the primary particles present in the surface portion of the secondary particles. When the barrier layer covers a portion of the surface of the primary particles and / or the secondary particles, the barrier layer can exist in an island shape.
[0146] The barrier layer covering the surface of the primary particle preferably has an average thickness of 0.1 nm to 1 μm.
[0147] When the average thickness of the barrier layer covering the primary particles is less than 0.1 nm, it may be difficult to fully suppress the dissolution of transition metals from the primary particles. On the other hand, when the average thickness of the barrier layer covering the primary particles is thicker than 1 μm, the surface dynamics of the primary particles may be reduced, or the conductivity of the secondary particles may be reduced.
[0148] In addition, when there is a concentration gradient of transition metal in the crystal grains constituting the primary particles, the region where the concentration gradient of transition metal exists may exist in a region adjacent to the surface of the crystal grains. In this case, the barrier layer may cover at least a portion of the surface of the primary particles, and the average thickness of the barrier layer is preferably 0.1 nm to 1 μm.
[0149] In one embodiment, the barrier layer may include a first oxide represented by the following Chemical Formula 2.
[0150] [Chemical formula 2]
[0151] Li c B d M3 e O f
[0152] Wherein, M3 is at least one selected from Ni, Mn, Co, Al, Nb, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd and Nd, 0≤c≤8, 0 <d≤8,0≤e≤8,2≤f≤13。
[0153] When the first oxide represented by the above chemical formula 2 is a borate-based compound or an LBO (lithium borate)-based compound, non-limiting examples of the above first oxide include B2O3, Li2O-B2O3, Li3BO3, Li2B4O7, Li2B2O7, Li2B8O 13 Etc. In addition, the first oxide may have a composition in which M3 as a different element is selectively doped into the borate-based compound or the lithium borate-based compound.
[0154] At this time, a gradient of decreasing concentration of at least one selected from B and M3 may be formed from the barrier layer toward the core of the lithium manganese-based oxide by diffusion and / or doping of the first oxide contained in the barrier layer.
[0155] The concentration gradient functions as a path for lithium ions to move inside the primary particles and between the primary particles, and thus, the efficiency of transport and diffusion of lithium ions through the primary particles can be improved.
[0156] In another embodiment, the barrier layer may further include a second oxide represented by the following Chemical Formula 3.
[0157] [Chemical formula 3]
[0158] Li g M4 h Oi
[0159] Among them, M4 is at least one selected from Ni, Mn, Co, Al, Nb, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd and Nd, 0≤g≤8, 0≤h≤8, 2≤i≤13, g and h are not 0 at the same time.
[0160] Non-limiting examples of the second oxide represented by the above Chemical Formula 3 include Li g Zr h O i , Li g Ti h O i , Li g Ni h O i , Li g Nb h O i , Li g Co h O i , Li g Si h O i , Li g Al h O i 、Co h O i , Mn h O i 、Al h O i 、Si h O i 、Zr h O i 、Ti h O i wait.
[0161] At this time, a gradient in which the concentration of M4 decreases from the barrier layer toward the core of the lithium manganese-based oxide may be formed by diffusion and / or doping of the second oxide included in the barrier layer.
[0162] In another embodiment, the barrier layer may include a third oxide represented by the following Chemical Formula 4.
[0163] [Chemical formula 4]
[0164] Li j M5 k (P l O m ) n
[0165] Among them, M5 is at least one selected from Ni, Mn, Co, Al, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, and Nd, 0 ≤ j ≤ 10, 0 ≤ k ≤ 8, 0 < l ≤ 4, 0 < m ≤ 10, 0 < n ≤ 13, and j and k are not both 0 at the same time.
[0166] Non-limiting examples of the above third oxide represented by the above chemical formula 4 may include Li j (P l O m ) n 、Li j Al k (P l O m ) n 、Al k (P l O m ) n 、(P l O m ) n 、Li j Mn k (P l O m ) n 、Mn k (P l O m ) n 、Li j Ni k (P l O m ) n 、Ni k (P l O m ) n and so on.
[0167] At this time, through the diffusion and / or doping, etc. of the above third oxide contained in the above barrier layer, a concentration gradient of at least one selected from M5 and P can be formed from the above barrier layer toward the core of the above lithium manganese-based oxide.
[0168] During the cycling of a lithium secondary battery using OLO, the reduction of charge / discharge capacity or voltage decay may be caused by a phase change resulting from the movement of transition metals in the lithium manganese-based oxide. For example, when the transition metals in the lithium manganese-based oxide with a layered crystal structure move in an unexpected direction and trigger a phase change, a spinel or a similar crystal structure appears in whole or in part in the lithium manganese-based oxide.
[0169] However, unlike the spinel phase formed by phase change caused by the movement of transition metals in the above-mentioned lithium manganese-based oxide, when the spinel phase is formed on the surface of the above-mentioned primary particles and / or the above-mentioned secondary particles while inducing crystal growth or grain growth of the primary particles constituting the above-mentioned lithium manganese-based oxide, the above-mentioned spinel phase not only contributes to surface stabilization of the above-mentioned lithium manganese-based oxide, but also can serve as a two-dimensional and / or three-dimensional path for lithium ion diffusion in the above-mentioned lithium manganese-based oxide.
[0170] Therefore, by allowing the spinel phase compound to exist in the above-mentioned barrier layer that exists to inhibit the dissolution of transition metals from the above-mentioned primary particles and / or the above-mentioned secondary particles, the above-mentioned lithium manganese-based oxide can exhibit an appropriate level of conductivity even if the above-mentioned barrier layer covers the surface of the above-mentioned primary particles and / or the above-mentioned secondary particles.
[0171] In addition, if necessary, the barrier layer may include at least two oxides selected from the first oxide to the third oxide, so as to effectively inhibit or alleviate the dissolution of transition metals from the lithium manganese-based oxide and improve the surface dynamic properties of the lithium manganese-based oxide.
[0172] On the other hand, generally, a ternary lithium composite oxide composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) containing a relatively excessive amount of nickel begins to show a sharp thermogravimetric loss at about 700° C., while a lithium-rich lithium manganese-based oxide is known to not show a thermogravimetric loss before about 900° C. Therefore, when a thermogravimetric analysis is performed on a lithium manganese-based oxide that has not undergone surface modification, no thermogravimetric loss occurs in the range of 400° C. to 700° C.
[0173] On the other hand, as defined herein, the lithium manganese-based oxide covering at least a portion of the surface of the primary particle and / or the secondary particle with the barrier layer begins to show thermal weight loss at about 500°C, and the thermal weight loss of the lithium manganese-based oxide can be confirmed at 700°C.
[0174] At this time, the thermogravimetric loss confirmed from the thermogravimetric analysis of the lithium manganese-based oxide may be caused by the components constituting the barrier layer. Therefore, the greater the barrier layer content in the lithium manganese-based oxide, the greater the thermogravimetric loss confirmed from the thermogravimetric analysis of the lithium manganese-based oxide may be.
[0175] When the thermal weight loss occurring when the lithium manganese-based oxide is subjected to a heat treatment in an inert gas atmosphere is analyzed, the difference (yx) between the weight loss rate (x) of the lithium manganese-based oxide at 400°C and the weight loss rate (y) at 700°C is preferably 0.03 wt% or more, and more preferably 0.10 wt% or more from the perspective of effectively inhibiting or reducing the dissolution of transition metals in the lithium manganese-based oxide.
[0176] The difference (yx) in the weight loss rate being less than 0.03 wt % means that a barrier layer for suppressing or alleviating the elution of transition metal is not sufficiently formed on the surface of the lithium manganese-based oxide.
[0177] In addition, the content of the main constituent element of the barrier layer calculated based on all metal elements except lithium present in the lithium manganese-based oxide is preferably greater than 0.1 mol% and less than 5 mol%. Here, when the first oxide is present in the barrier layer, the main constituent elements of the barrier layer are boron (B) and M3, when the second oxide is present in the barrier layer, the main constituent element of the barrier layer is M4, and when the third oxide is present in the barrier layer, the main constituent element of the barrier layer is M5. In addition, when any combination of the first oxide to the third oxide is present in the barrier layer, the main constituent element of the barrier layer is selected from boron (B), M3, M4 and M5.
[0178] The content of the main constituent elements of the barrier layer is less than 0.1 mol%, which means that the barrier layer for inhibiting or reducing the dissolution of transition metals is not fully formed on the surface of the lithium manganese-based oxide. Therefore, it is difficult to effectively prevent the impurities from being deposited on the positive electrode and / or the negative electrode due to the transition metals dissolved from the lithium manganese-based oxide, thereby accelerating the life degradation of the lithium secondary battery.
[0179] On the other hand, when the content of the main constituent elements of the above-mentioned barrier layer is greater than 5 mol%, the surface dynamic properties of the above-mentioned lithium manganese-based oxide may be reduced, and therefore, the electrochemical characteristics may be deteriorated compared to the case where the main constituent elements of the above-mentioned barrier layer are present in an appropriate content.
[0180] In addition, in order to effectively inhibit or reduce the dissolution of transition metals from the surface of the above-mentioned lithium manganese-based oxide without reducing the surface dynamic properties of the above-mentioned lithium manganese-based oxide, the content of the main constituent elements of the above-mentioned barrier layer calculated based on all metal elements other than lithium present in the above-mentioned lithium manganese-based oxide is more preferably 1±0.1 mol% or more and 3±0.1 mol% or less (specifically, 0.9 mol% to 3.1 mol%, more specifically, 0.98 mol% to 3.04 mol%).
[0181] Lithium secondary battery
[0182] According to another aspect of the present invention, a positive electrode including a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector may be provided, wherein the positive electrode active material layer may include the lithium manganese-based oxide according to various embodiments of the present invention as a positive electrode active material.
[0183] Therefore, the detailed description of the lithium manganese-based oxide will be omitted, and only the remaining components not mentioned above will be described below. In addition, for the sake of convenience, the lithium manganese-based oxide will be referred to as a positive electrode active material.
[0184] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or the surface of aluminum or stainless steel may be treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the binding force of the positive electrode active material. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a nonwoven body.
[0185] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition including the positive electrode active material, a conductive material, and optionally a binder as required, on the positive electrode current collector.
[0186] In this case, the content of the positive electrode active material can be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt % relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity performance can be shown, but it is not limited thereto.
[0187] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one of them or a mixture of two or more thereof can be used. The above-mentioned conductive material may be included in an amount of 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.
[0188] The above-mentioned binder serves to improve the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated ethylene propylene diene rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, 0.1% to 15% by weight of the above-mentioned binder may be included.
[0189] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.
[0190] The above-mentioned solvent can be a solvent commonly used in the technical field, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more of them can be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is as long as it can dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and has a viscosity that can show excellent thickness uniformity when applied for preparing the positive electrode.
[0191] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode collector.
[0192] In addition, according to another aspect of the present invention, an electrochemical device comprising the positive electrode described above can be provided. Specifically, the electrochemical device described above can be a battery, a capacitor, etc., and more specifically, can be a lithium secondary battery.
[0193] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separation membrane and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as the above description, so for convenience, the specific description is omitted, and only the remaining configuration not described above is described below.
[0194] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separation membrane; and a sealing member for sealing the battery container.
[0195] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0196] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 μm to 500 μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the collector. For example, it can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven body.
[0197] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode collector.
[0198] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; such as SiO β(0<β<2), SnO2, vanadium oxide, lithium vanadium oxide, metal oxides capable of being doped and dedoped with lithium; or composites containing the above metal compounds and carbon materials such as Si-C composites or Sn-C composites, etc., and one or a mixture of two or more of them can be used. In addition, as the above-mentioned negative electrode active material, a metal lithium film can also be used. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbons are soft carbon and hard carbon, and representative high-crystalline carbons are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kishgraphite), pyrolytic carbon (pyrolytic carbon), mesophase pitch based carbon fiber (mesophase pitch based carbon fiber), mesophase carbon microbeads (meso-carbon microbeads), mesophase pitch (Mesophase pitches) and petroleum or coal tar pitch derived cokes (petroleum or coal tar pitch derived cokes) and other high-temperature sintered carbons.
[0199] The negative electrode active material layer may contain 80 wt % to 99 wt % of the negative electrode active material, based on the total weight of the negative electrode active material layer.
[0200] The binder is a component that helps to bind the conductive material, the active material and the current collector. Usually, 0.1 wt % to 10 wt % of the binder can be added based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber, sulfonated ethylene propylene diene rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.
[0201] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10% by weight or less, preferably 5% by weight or less. There are no particular restrictions on such conductive materials as long as they do not induce chemical changes in the corresponding battery and have conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.
[0202] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode collector.
[0203] Furthermore, in another embodiment, the negative electrode active material layer can also be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it. The negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent. Alternatively, the negative electrode slurry composition is poured on a separate support and then a thin film obtained by peeling off the support is laminated on the negative electrode collector.
[0204] On the other hand, in the above-mentioned lithium secondary battery, the separation membrane is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the separation membrane commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and there is excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a separation membrane coated with a ceramic component and a polymer substance can also be used, which can be selectively used with a single layer or multilayer structure.
[0205] Furthermore, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc. that can be used when preparing lithium secondary batteries, but are not limited thereto.
[0206] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0207] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethylacetate, γ-butyrolactone, and ε-caprolactone; ether solvents such as dibutyl ether and tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methylethyl carbonate (MEC), ethylmethyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (EPC), etc. can be used. carbonate, PC) and other carbonate solvents; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (r is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be shown.
[0208] The above-mentioned lithium salt can be used without limitation as a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the above-mentioned lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. Preferably, the concentration of the above-mentioned lithium salt is used in the range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore, excellent electrolyte performance can be shown, and lithium ions can be effectively moved.
[0209] When the electrolyte used herein is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, or a halide solid electrolyte can be used, and preferably a sulfide solid electrolyte can be used.
[0210] As the material of the sulfide solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga and In) and S can be used. Examples of the above-mentioned sulfide solid electrolyte materials include Li2S-P2S5, Li2S-P2S-LiX (wherein X is a halogen element such as I or Cl), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (wherein m and n are integers, Z is Ge, Zn or Gam), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (wherein p and q are integers, and M is P, Si, Ge, B, Al, Ga or In), etc.
[0211] The solid electrolyte, preferably a sulfide-based solid electrolyte, may be in an amorphous state, may be in a crystalline state, or may be in a mixed state of the amorphous state and the crystalline state.
[0212] Examples of materials for oxide-based solid electrolytes include Li7La3Zr2O 12 , Li 7-x LqCy 1-x Nb x O 12 , Li 7- 3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3、Li 1+x Al x Ti 2-x (PO4)3、Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, Li3+x PO 4-x N x (LiPON), Li 2+2x Zn 1-x GeO4(LISICON), etc.
[0213] The solid electrolyte may be arranged between the positive electrode and the negative electrode as a separate layer (solid electrolyte layer). In addition, the solid electrolyte may be partially contained in the positive electrode active material layer of the positive electrode independently of the solid electrolyte layer, or the solid electrolyte may be partially contained in the negative electrode active material layer of the negative electrode independently of the solid electrolyte layer.
[0214] In addition to the above electrolyte components, the electrolyte may further include one or more additives such as halogenated alkylene carbonate compounds such as bisfluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.
[0215] As described above, the lithium secondary battery containing the positive electrode active material of the present invention stably shows excellent discharge capacity, output characteristics and life characteristics, and can therefore be used in portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).
[0216] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a prismatic shape, a pouch shape, a coin shape, etc. Also, preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.
[0217] According to another aspect of the present invention, a battery module including the above-mentioned lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.
[0218] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.
[0219] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only for illustrating the present invention, and the scope of the present invention should not be construed as being limited by these examples.
[0220] Preparation Example 1. Preparation of positive electrode active material
[0221] Example 1
[0222] (a) Precursor preparation
[0223] An aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while N2 gas was introduced into the reactor. After the reaction was completed, the Ni was washed and dehydrated to obtain a Ni 0.4 Mn 0.6 (OH)2 precursor.
[0224] (b) Precursor coating
[0225] In the reactor in which the precursor obtained in step (a) is stirred, an aqueous solution of NiSO4·6H2O, NaOH and NH4OH are added. At this time, NiSO4·6H2O is weighed to 5 mol% and then added. After the reaction is completed, washing and dehydration are performed, and then drying is performed at 150° C. for 14 hours to obtain a coated precursor.
[0226] (c) First heat treatment
[0227] The sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the precursor obtained in step (b) was heat-treated for 5 hours while maintaining 550°C, and then the furnace was cooled to obtain a precursor in an oxide state.
[0228] (d) Second heat treatment
[0229] A mixture is prepared by mixing the precursor in an oxide state obtained in step (c) with LiOH (molar ratio of lithium / (metal other than lithium) = 1.25) as a lithium raw material substance.
[0230] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 8 hours while maintaining 900°C, and then furnace-cooled to obtain a lithium-rich lithium manganese-based oxide.
[0231] As a result of TEM / EDS analysis of the above-mentioned lithium manganese-based oxide, it can be confirmed that by applying the nickel precursor in the above-mentioned step (b), a gradient is formed in which the nickel concentration increases from the center toward the surface and the manganese concentration decreases from the center toward the surface.
[0232] (e) Third heat treatment (forming a barrier layer)
[0233] After mixing the lithium manganese-based oxide obtained in the above step (d) and H3BO3 weighed so that the boron content of the lithium manganese-based oxide based on metal elements other than lithium is 1.0 mol%, the temperature is raised to 400°C at a rate of 4.4°C / min while maintaining an O2 atmosphere in a sintering furnace, and then heat-treated for 8 hours, classified and crushed to obtain a final product (average particle size of 3.5 μm) having a barrier layer containing a boron-containing compound formed on the surface.
[0234] Example 2
[0235] A positive electrode active material was prepared in the same manner as in Example 1 except that H 3 BO 3 weighing 2.0 mol % was used in the above step (e).
[0236] Example 3
[0237] A positive electrode active material was prepared in the same manner as in Example 1 except that H 3 BO 3 weighing 3.0 mol % was used in the above step (e).
[0238] Example 4
[0239] A positive electrode active material was prepared in the same manner as in Example 1, except that H 3 BO 3 weighed to 2.0 mol % was used in the above step (e) and the third heat treatment was performed with the final reaching temperature being 300° C.
[0240] Example 5
[0241] (e) Wet pretreatment
[0242] After the lithium manganese-based oxide obtained in step (d) of Example 1 and SiO2 weighed so that the silicon content of the lithium manganese-based oxide based on metal elements other than lithium is 1.0 mol% are mixed into distilled water during stirring, the mixture is stirred at 40° C. for 12 hours to obtain a lithium manganese-based oxide with SiO2 distributed on the surface.
[0243] (f) Third Heat Treatment (Barrier Layer Formation)
[0244] While maintaining an O2 atmosphere in a sintering furnace, the lithium manganese-based oxide obtained in step (e) is heated to 400°C at a rate of 4.4°C / min, then heat treated for 8 hours, classified and crushed to obtain a final product (average particle size of 3.5 μm) having a barrier layer containing a silicon-containing compound formed on the surface.
[0245] Example 6
[0246] (e) Wet pretreatment
[0247] After the lithium manganese-based oxide obtained in step (d) of Example 1 and NH4H2PO4 weighed so that the phosphorus content of the lithium manganese-based oxide based on metal elements other than lithium is 3.0 mol%, are added to distilled water during stirring, the mixture is stirred at 40°C for 12 hours to obtain a lithium manganese-based oxide with NH4H2PO4 distributed on the surface.
[0248] (f) Third Heat Treatment (Barrier Layer Formation)
[0249] While maintaining an O2 atmosphere in a sintering furnace, the lithium manganese-based oxide obtained in step (e) is heated to 400°C at a rate of 4.4°C / min, then heat treated for 8 hours, classified and crushed to obtain a final product (average particle size of 3.5 μm) having a barrier layer containing a phosphorus-containing compound formed on the surface.
[0250] Comparative Example 1
[0251] (a) Precursor preparation
[0252] A mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while N2 gas was introduced into the reactor. After the reaction was completed, the Ni with an average particle size of 3.5 μm was obtained by washing and dehydration. 0.4 Mn 0.6 (OH)2 precursor.
[0253] (b) First heat treatment
[0254] The sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the precursor obtained in step (a) was heat-treated for 5 hours while maintaining 550°C, and then the furnace was cooled to obtain a precursor in an oxide state.
[0255] (c) Second heat treatment
[0256] A mixture is prepared by mixing the precursor in an oxide state obtained in step (b) with LiOH (molar ratio of lithium / (metal other than lithium) = 1.25) as a lithium raw material substance.
[0257] Next, the sintering furnace in the O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat treated for 8 hours while maintaining 900°C, followed by furnace cooling, grading and pulverization to obtain a lithium-rich lithium manganese-based oxide (with an average particle size of 3.5 μm) as the final product.
[0258] Unlike the lithium manganese-based oxide according to Example 1, the lithium manganese-based oxide according to Comparative Example 1 was not subjected to precursor coating using nickel, and thus it was confirmed that no transition metal gradient was formed within the particles.
[0259] Comparative Example 2
[0260] (a) Precursor preparation
[0261] A mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while N2 gas was introduced into the reactor. After the reaction was completed, the Ni with an average particle size of 3.5 μm was obtained by washing and dehydration. 0.4 Mn 0.6 (OH)2 precursor.
[0262] (b) First heat treatment
[0263] The sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the precursor obtained in step (a) was heat-treated for 5 hours while maintaining 550°C, and then the furnace was cooled to obtain a precursor in an oxide state.
[0264] (c) Second heat treatment
[0265] A mixture is prepared by mixing the precursor in an oxide state obtained in step (b) with LiOH (molar ratio of lithium / (metal other than lithium) = 1.25) as a lithium raw material substance.
[0266] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 8 hours while maintaining 900°C, and then furnace-cooled to obtain a lithium-rich lithium manganese-based oxide.
[0267] (d) Third heat treatment (forming a barrier layer)
[0268] After mixing the lithium manganese-based oxide obtained in the above step (c) and H3BO3 weighed so that the boron content of the lithium manganese-based oxide based on metal elements other than lithium is 2.0 mol%, the temperature is raised to 400°C at a rate of 4.4°C / min while maintaining an O2 atmosphere in a sintering furnace, and then heat-treated for 8 hours, classified and crushed to obtain the final product (average particle size of 3.5 μm).
[0269] Unlike the lithium manganese-based oxide according to Example 1, the lithium manganese-based oxide according to Comparative Example 2 was not subjected to precursor coating using nickel, and thus it was confirmed that no transition metal gradient was formed within the particles.
[0270] Comparative Example 3
[0271] (a) Precursor preparation
[0272] A mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while N2 gas was introduced into the reactor. After the reaction was completed, the Ni with an average particle size of 3.5 μm was obtained by washing and dehydration. 0.4 Mn 0.6 (OH)2 precursor.
[0273] (b) Precursor coating
[0274] In the reactor in which the precursor obtained in step (a) is stirred, an aqueous solution of NiSO4·6H2O, NaOH and NH4OH are added. At this time, NiSO4·6H2O is weighed to 5 mol% and then added. After the reaction is completed, washing and dehydration are performed, and then drying is performed at 150° C. for 14 hours to obtain a coated precursor.
[0275] (c) First heat treatment
[0276] The sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the precursor obtained in step (b) was heat-treated for 5 hours while maintaining 550°C, and then the furnace was cooled to obtain a precursor in an oxide state.
[0277] (d) Second heat treatment
[0278] A mixture is prepared by mixing the precursor in an oxide state obtained in step (c) with LiOH (molar ratio of lithium / (metal other than lithium) = 1.25) as a lithium raw material substance.
[0279] Next, the sintering furnace in the O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat treated for 8 hours while maintaining 900°C, followed by furnace cooling, grading and pulverization to obtain a lithium-rich lithium manganese-based oxide (with an average particle size of 3.5 μm) as the final product.
[0280] As a result of TEM / EDS analysis of the above-mentioned lithium manganese-based oxide, it can be confirmed that by applying the nickel precursor in the above-mentioned step (b), a gradient is formed in which the nickel concentration increases from the center toward the surface and the manganese concentration decreases from the center toward the surface.
[0281] Comparative Example 4
[0282] (a) Precursor preparation
[0283] A mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while N2 gas was introduced into the reactor. After the reaction was completed, the Ni with an average particle size of 3.5 μm was obtained by washing and dehydration. 0.4 Mn 0.6 (OH)2 precursor.
[0284] (b) Precursor coating
[0285] In the reactor in which the precursor obtained in step (a) is stirred, an aqueous solution of NiSO4·6H2O, NaOH and NH4OH are added. At this time, NiSO4·6H2O is weighed to 5 mol% and then added. After the reaction is completed, washing and dehydration are performed, and then drying is performed at 150° C. for 14 hours to obtain a coated precursor.
[0286] (c) First heat treatment
[0287] The sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the precursor obtained in step (b) was heat-treated for 5 hours while maintaining 550°C, and then the furnace was cooled to obtain a precursor in an oxide state.
[0288] (d) Second heat treatment
[0289] A mixture is prepared by mixing the oxide precursor obtained in the above step (c), LiOH as a lithium raw material (molar ratio of lithium / (metal other than lithium) = 1.25) and WO3 weighed so that the W content based on metal elements other than lithium in the above precursor is 1.0 mol%.
[0290] Next, the sintering furnace in the O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat treated for 8 hours while maintaining 900°C, followed by furnace cooling, grading and pulverization to obtain a lithium-rich lithium manganese-based oxide (with an average particle size of 3.5 μm) as the final product.
[0291] As a result of TEM / EDS analysis of the above-mentioned lithium manganese-based oxide, it can be confirmed that by applying the nickel precursor in the above-mentioned step (b), a gradient is formed in which the nickel concentration increases from the center toward the surface and the manganese concentration decreases from the center toward the surface.
[0292] Reference Example 1
[0293] A positive electrode active material was prepared in the same manner as in Example 1, except that H 3 BO 3 weighed to 2.0 mol % was used in the above step (e) and the third heat treatment was performed with the final reaching temperature being 500° C.
[0294] Reference Example 2
[0295] A positive electrode active material was prepared in the same manner as in Example 1, except that H 3 BO 3 weighed to 2.0 mol % was used in the above step (e) and the third heat treatment was performed with the final reaching temperature being 600° C.
[0296] Reference Example 3
[0297] A positive electrode active material was prepared in the same manner as in Example 1, except that H 3 BO 3 weighed to 2.0 mol % was used in the above step (e) and the third heat treatment was performed with the final reaching temperature being 700° C.
[0298] Reference Example 4
[0299] A positive electrode active material was prepared in the same manner as in Example 1, except that H 3 BO 3 weighed to 0.1 mol % was used in the above step (e) and the third heat treatment was performed with the final reaching temperature being 300° C.
[0300] Reference Example 5
[0301] A positive electrode active material was prepared in the same manner as in Example 1, except that H 3 BO 3 weighed at 5.0 mol % was used in the above step (e) and the third heat treatment was performed with the final reaching temperature being 300° C.
[0302] Composition of lithium manganese-based oxide
[0303] The composition (molar ratio of each element) of the lithium manganese-based oxide contained in the positive electrode active material prepared according to Preparation Example 1 was measured by ICP, and the results are shown in Table 1 below.
[0304] Table 1
[0305]
[0306] *The lithium / metal molar ratio indicates the molar ratio of lithium to the entire elements other than lithium in the above-mentioned lithium manganese-based oxide.
[0307] *The element content (mol %) is calculated based on the entire elements except lithium in the above lithium manganese-based oxide.
[0308] Preparation Example 2. Fabrication of a lithium secondary battery (half-cell)
[0309] 90 wt % of each positive electrode active material prepared according to Preparation Example 1, 4.5 wt % of carbon black and 5.5 wt % of PVDF binder were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum film with a thickness of 15 μm and vacuum dried at 135° C. to prepare a positive electrode for a lithium secondary battery.
[0310] Relative to the above-mentioned positive electrode, lithium foil is used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25μm) is used as a separation membrane, and an electrolyte solution containing LiPF6 at a concentration of 1.15M in a solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate mixed in a volume ratio of 2:4:4 is used to prepare a half-cell.
[0311] Preparation Example 3. Preparation of lithium secondary battery (full battery)
[0312] 90 wt % of each positive electrode active material prepared according to Preparation Example 1, 4.5 wt % of carbon black and 5.5 wt % of PVDF binder were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum film with a thickness of 15 μm and vacuum dried at 135° C. to prepare a positive electrode for a lithium secondary battery.
[0313] Relative to the above-mentioned positive electrode, a graphite electrode was used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separation membrane, and a full battery was prepared using an electrolyte solution in which LiP F6 was present at a concentration of 1.15 M in a solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate mixed in a volume ratio of 2:4:4.
[0314] Experimental Example 1. XPS Analysis of Positive Electrode Active Material
[0315] The lithium manganese-based oxide selected from each of the positive electrode active materials prepared according to Preparation Example 1 was subjected to XPS analysis to measure the content of the target element contained in the above lithium manganese-based oxide.
[0316] Specifically, using the XPS depth profile analysis method (ion energy: 2000 eV, spot size: 200 μm), the change in target element content from the surface of the lithium manganese-based oxide (secondary particles) toward the center of the lithium manganese-based oxide (secondary particles) was measured while gradually increasing the etching time of the lithium manganese-based oxide surface.
[0317] The above XPS analysis results are shown in Tables 2 and 3 below.
[0318] Table 2
[0319]
[0320] *The content (atomic %) of the target element is calculated based on all elements except lithium in the above lithium manganese-based oxide.
[0321] Referring to the results in Table 2 above, it can be seen that the content of the target element present in the surface portion of the lithium manganese-based oxide (secondary particle) according to Example 1, Example 2, Example 5 and Example 6 is 20 atomic % or more. It is estimated that the reason why the content of the target element derived from the raw material used in the third heat treatment in the surface portion of the above lithium manganese-based oxide (secondary particle) is 20 atomic % or more is because a barrier layer is formed on the surface portion of the above lithium manganese-based oxide (secondary particle).
[0322] On the other hand, it can be confirmed that in the case of Comparative Example 4, the measured target element content decreases with the increase of etching time, but the content of the target element present on the surface of the lithium manganese-based oxide (secondary particles) is excessively smaller than that of the lithium manganese-based oxide according to Examples 1, 2, 5 and 6.
[0323] The above results show that the target element from the raw material used in the second heat treatment step does not exist as a barrier layer on the surface of the lithium manganese-based oxide (secondary particles), but is mostly doped into the lithium manganese-based oxide (especially primary particles). In addition, as the etching time increases, the content of the target element decreases, which is also expected to be caused by the doping and diffusion of the target element from the surface of the lithium manganese-based oxide to the center.
[0324] Therefore, it was confirmed that the physical barrier layer that can function as a barrier layer does not actually exist on the surface of the lithium manganese-based oxide (secondary particles) according to Comparative Example 4.
[0325] Table 3
[0326]
[0327] *The target element content is calculated based on the sum of the contents of Ni and Mn in all elements other than lithium in the above lithium manganese-based oxide as 100.
[0328] Referring to the results of Table 3 above, it can be confirmed that when the lithium manganese-based oxide according to Example 1 is prepared, the nickel precursor coating is performed to form a gradient in which the nickel concentration increases from the center toward the surface and the manganese concentration decreases from the center toward the surface.
[0329] Experimental Example 2. Thermogravimetric analysis (TGA) of positive electrode active material
[0330] The lithium manganese-based oxide selected from each positive electrode active material prepared according to Preparation Example 1 was subjected to thermal weight loss analysis to determine whether an appropriate level of barrier layer was formed on the surface of the primary particles and / or secondary particles constituting the above lithium manganese-based oxide.
[0331] TGA analysis was performed under the following conditions, and the results of TGA analysis are shown in Table 4 below.
[0332] Sample: 65 mg of lithium manganese oxide
[0333] Measurement atmosphere: Ar gas (gas flow rate: 60 ml / min)
[0334] Measurement conditions: from 30℃ to 900℃ at a rate of 10℃ / min
[0335] Table 4
[0336]
[0337]
[0338] Referring to the results in Table 4 above, it can be confirmed that the lithium manganese-based oxide in Comparative Example 3 actually does not undergo thermogravimetric loss at 400° C. and 700° C., taking into account the error range. In other words, it can be seen that this is consistent with the trend of the thermogravimetric analysis results that general lithium manganese-based oxides do not undergo thermogravimetric loss before about 900° C.
[0339] On the other hand, it was confirmed that the lithium manganese-based oxides according to Examples 1, 2, and 6 began to experience thermogravimetric loss at about 500° C. to 600° C. In addition, it was confirmed that as the content of the barrier layer present in the lithium manganese-based oxide increased, the thermogravimetric loss confirmed from the thermogravimetric analysis of the lithium manganese-based oxide also increased.
[0340] Experimental Example 3. Evaluation of electrochemical characteristics of lithium secondary battery (half-cell)
[0341] The lithium secondary battery (half-cell) prepared according to Preparation Example 2 was subjected to a charge / discharge experiment using an electrochemical analyzer (Toyo, Toscat-3100) at 25°C, a voltage range of 2.0 V to 4.6 V, and a discharge rate of 0.1 C to 5.0 C to measure the initial charge capacity, initial discharge capacity, initial reversible efficiency, and rate characteristics (discharge capacity ratio; rate capability, C-rate).
[0342] The above measurement results are shown in Table 5 below.
[0343] Table 5
[0344]
[0345] Referring to the half-cell evaluation results in Table 5 above, it can be confirmed that in the case of Comparative Examples 1 and 2 where the transition metal does not present a concentration gradient from the center to the surface of the particle, regardless of whether there is a barrier layer on the particle surface, the discharge capacity ratio is lower than that of the lithium secondary battery using the lithium manganese-based oxide according to the embodiment as the positive electrode active material.
[0346] In the case of Reference Examples 1 to 3 in which the third heat treatment temperature for forming the barrier layer was high, it was confirmed that the electrochemical properties such as the initial discharge capacity and the discharge capacity ratio were deteriorated. The above results are expected to be due to the fact that the lithium manganese-based oxide was damaged, such as the transition metal concentration gradient in the particles was destroyed, as the third heat treatment temperature was excessively increased.
[0347] On the other hand, Reference Examples 4 and 5 show generally better electrochemical properties than Comparative Examples 1 to 4, but due to too little or too much raw material forming the barrier layer, they are somewhat lacking in the effect of improving the rate characteristics compared to the embodiments.
[0348] Experimental Example 4. Evaluation of electrochemical characteristics of lithium secondary battery (full battery)
[0349] For the lithium secondary battery (full battery) in Preparation Example 3 prepared using the positive electrode active material in Example 2, Comparative Example 2, Comparative Example 3 and Comparative Example 4, an electrochemical analyzer (Toyo, Toscat-3100) was used to complete 6 cycles of formation at 25°C, a voltage range of 2.0V to 4.6V and 0.2C / 0.2C, and then charged / discharged 500 times at 25°C, a voltage range of 2.0V to 4.6V and 1C / 1C. Through the above charge / discharge experiment, the initial (first cycle) discharge capacity, the discharge capacity ratio of the 100th cycle, the 300th cycle and the 500th cycle relative to the initial discharge capacity (cycle capacity retention; capacity retention) was measured.
[0350] The above measurement results are shown in Table 6 below.
[0351] Table 6
[0352]
[0353] Referring to the full battery evaluation results in Table 6 above, it can be confirmed that in the case of Comparative Examples 3 and 4, where the transition metal has a concentration gradient from the center of the particle to the surface but there is no barrier layer on the particle surface, the cycle capacity retention rate drops sharply. It is predicted that the above results are due to the abnormal resistance phenomenon of the negative electrode as the transition metal dissolves from the above lithium manganese-based oxide, thereby accelerating the life degradation of the lithium secondary battery.
[0354] On the other hand, in the case of Comparative Example 2 where there is no transition metal concentration gradient from the center to the surface of the particle but a barrier layer is formed on the particle surface, the cycle capacity retention rate is improved compared with Comparative Example 3 because the impedance anomaly phenomenon occurring in Comparative Example 3 is reduced.
[0355] On the other hand, it can be confirmed that in the case of Example 2, in which the transition metal presents a concentration gradient from the center to the surface of the particle and a barrier layer is formed on the surface of the particle, the transition metal in the lithium manganese-based oxide is prevented from dissolving, and the kinetic properties of the particle surface are improved, thereby improving the electrochemical properties. Therefore, its cycle capacity retention rate is better than that of Comparative Example 2.
[0356] Experimental Example 5. Experiment on the dissolution of transition metals
[0357] For the lithium secondary battery (full battery) prepared in Preparation Example 3 using the positive electrode active material according to Example 2, Comparative Example 2, Comparative Example 3 and Comparative Example 4, an electrochemical analyzer (Toyo, Toscat-3100) was used to complete 6 cycles of formation at 25°C, a voltage range of 2.0V to 4.6V and 0.2C / 0.2C, and then 2 cycles of charge / discharge were performed at 25°C, a voltage range of 2.0V to 4.6V and 0.05C / 0.05C for stabilization. Then, after the full battery was disassembled, the negative electrode was cleaned with a diethyl carbonate solvent, vacuum dried at 60°C, and then recovered.
[0358] Only the negative electrode active material was separated from the recovered copper foil (current collector) of the recovered negative electrode, and the separated negative electrode active material was subjected to ICP analysis to measure the contents of manganese and nickel contained in the negative electrode active material.
[0359] In addition, for the lithium secondary battery (full battery) prepared in Preparation Example 3 using the positive electrode active material according to Example 2, Comparative Example 2, Comparative Example 3 and Comparative Example 4, an electrochemical analyzer (Toyo, Toscat-3100) was used to complete 6 cycles of formation at 25°C, a voltage range of 2.0V to 4.6V and 0.2C / 0.2C, and then charged / discharged 500 times at 25°C, a voltage range of 2.0V to 4.6V and 1C / 1C. Subsequently, it was stabilized by performing secondary cycle charge / discharge at 25°C, a voltage range of 2.0V to 4.6V and 0.05C / 0.05C. Then, after the full battery was disassembled, the negative electrode was cleaned with a diethyl carbonate solvent, vacuum dried at 60°C, and then recovered.
[0360] Only the negative electrode active material was separated from the recovered copper foil (current collector) of the recovered negative electrode, and the separated negative electrode active material was subjected to ICP analysis to measure the contents of manganese and nickel contained in the negative electrode active material.
[0361] The above measurement results are shown in Table 7 below.
[0362] Table 7
[0363]
[0364] Referring to the results of Table 7 above, as expected in Experimental Example 4, it can be confirmed that the rapid life degradation of Comparative Examples 3 and 4 is due to the increase in the content of transition metal deposited on the negative electrode active material after formation or after 500 charge / discharge cycles.
[0365] On the other hand, in the case of Comparative Example 2 in which the barrier layer was formed in the same manner as in Example 2, it was confirmed that the content of transition metal eluted toward the negative electrode side was greater than that of Example 2. The above results are expected to be because the lithium manganese-based oxide according to Example 2 formed a concentration gradient in which the content of transition metals with relatively low elution probability was higher than the content of other transition metals in the region corresponding to the particle surface (shell), while the lithium manganese-based oxide according to Comparative Example 2 did not form a gradient distribution of the transition metal concentration from the center of the particle to the surface.
[0366] Although the embodiments of the present invention are described above, those skilled in the art will understand that various modifications and changes can be made to the present invention by adding, modifying, deleting, increasing, etc., without departing from the scope of the idea of the present invention as described in the claims, and these also fall within the scope of the rights of the present invention.
Claims
1. A positive electrode active material, which is a lithium manganese-based oxide positive electrode active material including a phase belonging to the C2 / m space group and a phase belonging to the R-3m space group solid solution or complex, wherein the positive electrode active material is characterized in that: The lithium manganese-based oxide is a core-shell particle in which at least one transition metal constituting the lithium manganese-based oxide has a concentration gradient from the core to the shell. And there is a barrier layer covering at least a portion of the surface of the shell.
2. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide in the positive electrode active material exists as secondary particles formed by aggregation of a plurality of primary particles. The secondary particles are core-shell particles in which at least one transition metal presents a concentration gradient from the center of the secondary particles toward the surface of the secondary particles. The barrier layer exists in a manner covering at least a portion of the surface of the secondary particle. The barrier layer suppresses or reduces the dissolution of transition metal from the secondary particles.
3. The positive electrode active material according to claim 2, characterized in that The grain boundaries between adjacent primary particles are defined. The barrier layer exists in a state of being diffused from the surface portion of the secondary particle toward the center portion of the secondary particle along the grain boundary.
4. The positive electrode active material according to claim 2, characterized in that The region where the transition metal concentration gradient exists is located within the shell of the secondary particle. The average thickness of the shell is 0.1 nm to 5 μm, and the average thickness of the barrier layer is 0.1 nm to 1 μm.
5. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide in the positive electrode active material exists in at least one form selected from a single primary particle and a secondary particle formed by aggregation of a plurality of primary particles. The primary particles are core-shell particles in which at least one transition metal has a concentration gradient from the center of the primary particles toward the surface of the primary particles. The barrier layer exists in a manner covering at least a portion of the surface of the primary particle. The barrier layer suppresses or reduces the dissolution of the transition metal from the primary particles.
6. The positive electrode active material according to claim 5, characterized in that The region where the transition metal concentration gradient exists is located within the shell of the primary particle. The average thickness of the shell is 0.1 nm to 2 μm, and the average thickness of the barrier layer is 0.1 nm to 1 μm.
7. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide includes primary particles having at least one crystal grain, At least one transition metal in the crystal grains has a concentration gradient from the center of the crystal grains to the surface of the crystal grains, The barrier layer exists in a manner covering at least a portion of the surface of the primary particle. The barrier layer suppresses or reduces the dissolution of the transition metal from the primary particles.
8. The positive electrode active material according to claim 7, characterized in that The region where the transition metal concentration gradient exists is located in the region adjacent to the surface of the crystal grain. The average thickness of the region where the transition metal concentration gradient exists in the grain is 0.1 nm to 500 nm, and the average thickness of the barrier layer is 0.1 nm to 1 μm.
9. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide is represented by the following chemical formula 1: [Chemical formula 1] He(He a M1 x M2 y )O 2-b X b (Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd and Nd, M2 and M1 are not repeated, X is a halogen that can replace at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, <a≤0.7、0≤b≤0.1、0<x≤1、0≤y<1、0<x+y≤1)。 10. The positive electrode active material according to claim 9, characterized in that The lithium manganese-based oxide is a core-shell particle in which at least one selected from nickel and manganese has a concentration gradient from the core to the shell.
11. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide is represented by the following chemical formula 1-1: [Chemical formula 1-1] <h2 style=";text-align:left;direction:ltr">rLi2MnO3·(1-r)Li<h2 style=";text-align:left;direction:ltr"> a' <h2 style=";text-align:left;direction:ltr"> M1<h2 style=";text-align:left;direction:ltr"> x' <h2 style=";text-align:left;direction:ltr"> M2<h2 style=";text-align:left;direction:ltr"> y' <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 2-b' <h2 style=";text-align:left;direction:ltr"> X<h2 style=";text-align:left;direction:ltr"> b' (Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd and Nd, M2 and M1 are not repeated, X is a halogen that can replace at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, <r≤0.7、0<a'≤1、0≤b'≤0.1、0<x'≤1、0≤y'<1、0<x'+y'≤1)。 12. The positive electrode active material according to claim 11, characterized in that The lithium manganese-based oxide is a core-shell particle in which at least one selected from nickel and manganese has a concentration gradient from the core to the shell.
13. The positive electrode active material according to claim 1, characterized in that When the thermogravimetric loss of the lithium manganese-based oxide is analyzed under an inert gas atmosphere, the lithium manganese-based oxide has a thermogravimetric loss at 700° C.
14. The positive electrode active material according to claim 13, characterized in that The difference (yx) between the weight loss rate (x) of the lithium manganese-based oxide at 400° C. and the weight loss rate (y) of the lithium manganese-based oxide at 700° C. is 0.03 wt % or more.
15. The positive electrode active material according to claim 1, characterized in that The barrier layer includes a first oxide represented by the following chemical formula 2: [Chemical formula 2] Li c B d M3 e O f (wherein, M3 is at least one selected from Ni, Mn, Co, Al, Nb, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, and Nd; 0 ≤ c ≤ 8, 0 < d ≤ 8, 0 ≤ e ≤ 8, 2 ≤ f ≤ 13).
16. The positive electrode active material according to claim 15, wherein a gradient in which the concentration of at least one selected from B and M3 decreases from the above-mentioned barrier layer toward the core of the above-mentioned lithium manganese-based oxide is formed.
17. The positive electrode active material according to claim 1, wherein the above-mentioned barrier layer includes a second oxide represented by Chemical Formula 3 below: [Chemical Formula 3] Li g M4 h About i (wherein, M4 is at least one selected from Ni, Mn, Co, Al, Nb, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, and Nd; 0 ≤ g ≤ 8, 0 ≤ h ≤ 8, 2 ≤ i ≤ 13, provided that g and h are not both 0).
18. The positive electrode active material according to claim 17, wherein a gradient in which the concentration of M4 decreases from the above-mentioned barrier layer toward the core of the above-mentioned lithium manganese-based oxide is formed.
19. The positive electrode active material according to claim 1, wherein the above-mentioned barrier layer includes a third oxide represented by Chemical Formula 4 below: [Chemical Formula 4] Li j M5 k (P l Oh m ) n (wherein, M5 is at least one selected from Ni, Mn, Co, Al, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, and Nd; 0 ≤ j ≤ 10, 0 ≤ k ≤ 8, 0 < l ≤ 4, 0 < m ≤ 10, 0 < n ≤ 13, provided that j and k are not both 0).
20. The positive electrode active material according to claim 19, wherein a gradient in which the concentration of at least one selected from M5 and P decreases from the above-mentioned barrier layer toward the core of the above-mentioned lithium manganese-based oxide is formed.
21. The positive electrode active material according to claim 1, wherein a spinel phase exists in at least a part of the surface of the above-mentioned shell.
22. A positive electrode, characterized in that: Comprising the positive electrode active material according to any one of claims 1 to 21.
23. A lithium secondary battery, characterized in that: Using the positive electrode according to claim 22.
Citation Information
Patent Citations
Cathode active material, method for preparing the same, and lithium secondary batteries comprising the same
KR1020150069334A
Positive electrode active material for lithium secondary battery, preparation method for same, and lithium secondary battery comprising same
CN106797049A
Hollow spherical cathode material with radially grown and arranged crystal grains and preparation method thereof
CN110676451A
Preparation method of double-shell spherical lithium-rich layered oxide positive electrode material with radially arranged crystal grains
CN111584842A
Cathode active material and battery using the same
JP2020043053A